Promotores de adolescentes infractores. - Carrión Avelino, José Andrés (2015)
In this research, has defended the hypothesis that the typicality of promoting youth criminal offense in the Ecuadorian organic whole code has encouraged the growth rate of offenses involving adolescents, keeping in distress to society, without any objective answer about a possible solution. It has also been considered with great courage that promoting adolescent offenders, infringes the right of children to free development of personality, and make their own decisions about their life project, since theories that explain juvenile crime accept that adolescents are very likely to be influenced by others to the commission of offenses.